Neuroprotection Against NMDA-Induced Retinal Damage by Philanthotoxin-343 Involves Reduced Nitrosative Stress - Mohamad Haiqal Nizar Mohamad; Izuddin Fahmy Abu; Muhammad Fattah Fazel; Renu Agarwal; Igor Iezhitsa; Norsham Juliana; Ian R. Mellor; Henrik Franzyk (frontiers, 2024)
Indexed by WOS/Scopus / ERA